Karyotypic studies in wild species of arachis (leguminosae) belonging to sections erectoides, procumbentes and rhizomatosae - Ortiz, Alejandra Marcela (2013)
Karyotypes of three diploid species belonging to sections Erectoides (Arachis hermannii), Procumbentes (A. rigonii) and Rhizomatosae (A. burkartii) were analyzed by Feulgen´s technique. The karyotype formula was different in each of the taxa analyzed: 2n=2x=16m+4sm in A. hermannii, 2n=2x=18m+2sm in A. rigonii, and 2n=2x=20m in A. burkartii. All species had a pair of satellited chromosomes, which corresponded to type 2 in A. hermannii, type 9 in A. rigonii, and type 8 in A. burkartii. Arachis hermannii and A. rigonii presented chromosomal features similar to those of the other species included in their respective sections. However, A. burkartii showed chromosome characteristics different from those found in the rest of the species of section Rhizomatosae.